2020
DOI: 10.1051/e3sconf/202016401035
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the infrastructure of the waste processing cluster

Abstract: In the Strategy for socio-economic development of the Voronezh region for the period until 2035, one of the main problems in the field of waste management is the rather low level of waste involvement in economic turnover. Improving of the current situation is expected by introducing resource-saving and low-waste technologies; implementation of a territorial and regional waste management program, as well as through the creation of an environmentally friendly waste management infrastructure. The implementation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…This is in line with the focus on smart water infrastructures and the reconfigurable test-beds for research in water infrastructures management, which are essential components of advanced waste management infrastructure (Ledesma et al, 2021). Additionally, the need for a transition to a new waste management system has been identified, indicating the recognition of the main problems and the potential for improvement in waste management infrastructure (Serebryakova et al, 2020). The optimization of waste collection routes using AI algorithms is a crucial aspect of waste management.…”
Section: Introductionmentioning
confidence: 65%
“…This is in line with the focus on smart water infrastructures and the reconfigurable test-beds for research in water infrastructures management, which are essential components of advanced waste management infrastructure (Ledesma et al, 2021). Additionally, the need for a transition to a new waste management system has been identified, indicating the recognition of the main problems and the potential for improvement in waste management infrastructure (Serebryakova et al, 2020). The optimization of waste collection routes using AI algorithms is a crucial aspect of waste management.…”
Section: Introductionmentioning
confidence: 65%
“…Analyzing the positive impact of the development of the virtual labor market, the researchers emphasize the possibility of solving a number of urgent problems. These include the adaptation of white collars released in the process of digitalization; prevention of stagnant unemployment; involvement of socially vulnerable strata of the population in the economically active population, solution of environmental problems [1,[14][15][16][17]. Taking into account the possibilities of the virtual labor market, it was concluded that it can help to find ways to adapt to such serious challenges from the external environment as changing the nature of many professions or their complete disappearance [18][19][20], shortening the life cycle of a profession and strengthening the role of competencies, the polarization of the employed and the gradual displacement of professions requiring an average level of qualifications [21], an increase in the period of retirement [22].…”
Section: Methodsmentioning
confidence: 99%